Convective Flow of Radiative Maxwell Nanofluid with Variable Thermo-Physical Properties - Borgohain, Debozani (Trends in Sciences, 2022)
In this article, analysis has been executed to find the impact of radiation, varied thermal conductivity and varied viscosity on the steady 2 dimensional flows of nanoparticles existing Maxwell fluid past a flat surface that can be stretched. The partial differential equations which govern this flow are modified by using similarity transformations in order to form ordinary differential equations. Employing bvp4c of MATLAB software the transformed equations are solved and the results for velocity, temperature and species concentration are depicted through graphs for varying parametric values. Comparisons with previous published data of analytical methods are carried out, thereby validating the present numerical results. It has been observed that thermal conductivity as well as viscosity enhances the temperature of the fluid and nanoparticles species concentration. Also the nanoparticles existence in the fluid slows down the fluid motion. In various engineering processes and nanoscience technology, the inferences of this present study can find its applications. HIGHLIGHTS Investigation has been carried out on a 2 dimensional steady flow of upper-convected Maxwell fluid under the existence of the radiation and nanoparticles The thermo-physical properties of the fluid flow such as thermal conductivity and viscosity are taken as variable quantity Bvp4c solver of the software MATLAB has been used to solve the governing transformed ODEs With the rise in thermal conductivity and fluid viscosity, the temperature of the fluid boost up The existence of nanoparticles in the fluid results in deceleration of the fluid motion